A Partial Skeleton of the Fossil Great Ape Hispanopithecus laietanus from Can Feu and the Mosaic Evolution of Crown-Hominoid Positional Behaviors - Alba, David M.; Almécija, Sergio; Casanovas-Vilar, Isaac; Méndez, Josep M.; Moyà-Solà, Salvador (PLOS ONE, 2012)
The extinct dryopithecine Hispanopithecus (Primates: Hominidae), from the Late Miocene of Europe, is the oldest fossil great ape displaying an orthograde body plan coupled with unambiguous suspensory adaptations. On the basis of hand morphology, Hispanopithecus laietanus has been considered to primitively retain adaptations to above-branch quadrupedalism–thus displaying a locomotor repertoire unknown among extant or fossil hominoids, which has been considered unlikely by some researchers. Here we describe a partial skeleton of H. laietanus from the Vallesian (MN9) locality of Can Feu 1 (Vallès-Penedès Basin, NE Iberian Peninsula), with an estimated age of 10.0-9.7 Ma. It includes dentognathic and postcranial remains of a single, female adult individual, with an estimated body mass of 22–25 kg. The postcranial remains of the rib cage, shoulder girdle and forelimb show a mixture of monkey-like and modern-hominoid-like features. In turn, the proximal morphology of the ulna–most completely preserved in the Can Feu skeleton than among previously-available remains–indicates the possession of an elbow complex suitable for preserving stability along the full range of flexion/extension and enabling a broad range of pronation/supination. Such features, suitable for suspensory behaviors, are however combined with an olecranon morphology that is functionally related to quadrupedalism. Overall, when all the available postcranial evidence for H. laietanus is considered, it emerges that this taxon displayed a locomotor repertoire currently unknown among other apes (extant or extinct alike), uniquely combining suspensory-related features with primitively-retained adaptations to above-branch palmigrady. Despite phylogenetic uncertainties, Hispanopithecus is invariably considered an extinct member of the great-ape-and-human clade. Therefore, the combination of quadrupedal and suspensory adaptations in this Miocene crown hominoid clearly evidences the mosaic nature of locomotor evolution in the Hominoidea, as well as the impossibility to reconstruct the ancestral locomotor repertoires for crown hominoid subclades on the basis of extant taxa alone.